Fouling of nanofiltration and reverse osmosis membranes by organic macromolecules and their mixtures - Wang, YiNing (2011)
The performance of nanofiltration (NF) and reverse osmosis (RO) membranes can be significantly restricted due to fouling by organic macromolecules during water and wastewater treatment. Fouling causes a reduction of the membrane permeation flux, demands more frequent cleaning, and shortens the membrane life span. Proteins are among the main macromolecules that foul NF and RO membranes. Protein fouling (single, binary mixture and protein-polysaccharide mixture) of NF and RO membranes was systematically investigated in the current work.